2007
DOI: 10.1016/j.ejvs.2007.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Ischemia after Endovascular Repair of the Descending Thoracic Aorta in a Sheep Model

Abstract: In sheep, incidence of histological and clinical ischemic injury of the spinal cord following endografting was very low. Complete thoracic aortic stent-grafting was feasible without permanent neurologic deficit. Following endovascular coverage or clipping of their origins, there is retrograde filling of the intercostal arteries which remain patent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 51 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…14 In an animal model, Böckler et al demonstrated that endovascular repair is associated with lower rates of spinal cord ischaemia and paraplegia than aortic cross-clamping. 29 These findings were confirmed in human by Carroccio et al 30 This hypothetical advantage was likely balanced in our series by the increased risk of spinal cord ischaemia related to the high incidence of prior descending, abdominal or thoraco-abdominal aortic graft repairs in the patients we selected for hybrid TAAA repair. 25 However, the problem of paraplegia has not been eliminated by hybrid TAAA repair and extensive coverage of the thoracoabdominal aorta could be identified as the cause of a still significant rate of spinal cord complications.…”
Section: Spinal Cord Ischaemiasupporting
confidence: 80%
“…14 In an animal model, Böckler et al demonstrated that endovascular repair is associated with lower rates of spinal cord ischaemia and paraplegia than aortic cross-clamping. 29 These findings were confirmed in human by Carroccio et al 30 This hypothetical advantage was likely balanced in our series by the increased risk of spinal cord ischaemia related to the high incidence of prior descending, abdominal or thoraco-abdominal aortic graft repairs in the patients we selected for hybrid TAAA repair. 25 However, the problem of paraplegia has not been eliminated by hybrid TAAA repair and extensive coverage of the thoracoabdominal aorta could be identified as the cause of a still significant rate of spinal cord complications.…”
Section: Spinal Cord Ischaemiasupporting
confidence: 80%
“…There are numerous reports of the use of the sheep model to study spinal cord injury. Kaplan [32], Moomiaie [33], and Bockler [34] describe the use of the sheep model for detecting interruption of spinal cord blood flow during aortic cross-clamping. Numerous reports exist for the testing of the epidural approach for anesthesia and for attempts at protecting against spinal ischemia in sheep [35-39].…”
Section: Methodsmentioning
confidence: 99%
“…An important treatment for this injury is intradural or epidural spinal cord stimulation using electrodes to alleviate post-SCI chronic pain and spasticity. Sheep have been used to test the efficacy and safety of these implantable devices [91,92] . Several factors require consideration: proximity to the stimulation area, magnitude of the stimuli, durability and longevity of the device, and prevention of ischemic effects due to pressure from the device [91,92] .…”
Section: Spinal Cord Injurymentioning
confidence: 99%